Pengaruh GCG, Leverage, Pengungkapan CSR terhadap Performance Financial pada Perbankan Syariah di Indonesia dengan Ukuran Perusahaan sebagai Variabel Moderasi - Ghina Kemala Dewi; Indah Fitri Yani; Yohana Yohana; Nawang Kalbuana; Muhammad Tho’in (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to determine how the effect of GCG, leverage, CSR disclosure on financial performance with firm size as a moderating variable. The population in this study is Islamic banking registered with Bank Indonesia (BI) during the 2015-2019 period. The technique of determining the sample in this study is purposive sampling technique and for data analysis this study uses multiple linear analysis techniques. This study reveals that GCG has no significant effect on financial performance, leverage has a positive and significant effect on financial performance, CSR disclosure has a positive and significant effect on financial performance, firm size has no effect on the effect of GCG on financial performance, firm size has no effect on leverage on financial performance. financial performance, and firm size has a negative effect on the effect of CSR disclosure on financial performance.